2000
DOI: 10.1073/pnas.150040497
|View full text |Cite
|
Sign up to set email alerts
|

Reelin controls position of autonomic neurons in the spinal cord

Abstract: T he autosomal recessive mouse mutant reeler, which exhibits ataxia of gait, dystonic posture, and tremor (1), has provided a genetic model for neural development for half a century (2-4). Characteristic of the reeler mutant are abnormal lamination of the cerebral, cerebellar, and hippocampal cortices and neuronal ectopia in several brainstem nuclei (5-13). The gene Reln, the mutation of which is responsible for the reeler phenotype, has recently been cloned (14). Its protein product, reelin, has been identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
122
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(136 citation statements)
references
References 44 publications
13
122
1
Order By: Relevance
“…Many Reelin-responsive neurons fail to meet this criterion, such as Purkinje cells, and some cortical neurons, which do not migrate far enough when Reelin or downstream components of the pathway are missing. However, the preganglionic autonomic spinal cord neurons (AMNs) appear to migrate beyond their target zones in the absence of Reelin (Phelps et al, 2002;Yip et al, 2000). The migratory pathway of these neurons is complex.…”
Section: Discussionmentioning
confidence: 99%
“…Many Reelin-responsive neurons fail to meet this criterion, such as Purkinje cells, and some cortical neurons, which do not migrate far enough when Reelin or downstream components of the pathway are missing. However, the preganglionic autonomic spinal cord neurons (AMNs) appear to migrate beyond their target zones in the absence of Reelin (Phelps et al, 2002;Yip et al, 2000). The migratory pathway of these neurons is complex.…”
Section: Discussionmentioning
confidence: 99%
“…11 Further studies have identified RELN as necessary for proper formation of brain structures by directing migration of neuronal precursors. [12][13][14][15][16][17][18][19] These suggestive developmental roles for RELN correlate with RELN abnormalities in several neurogenetic diseases. RELN mRNA and protein levels are significantly reduced in multiple brain areas of patients with schizophrenia 20,21 and bipolar disorder with psychosis.…”
mentioning
confidence: 86%
“…Indeed, radial glia morphology or Blbp content is normal in the spinal cord of reeler mice (data not shown) as is radial cell migration. Interestingly, only the tangential migration of preganglionic neurons is affected in the spinal cord of reelindeficient mice (Yip et al, 2000;Phelps et al, 2002). Thus, the effect of reelin on tangential cell migration seems to be mediated in a radial glia independent manner, potentially by signaling directly to the migrating neurons.…”
Section: Radial Glia Defects and Neuronal Migrationmentioning
confidence: 99%